Pengaruh Metode Bercerita Bermedia Audio-Visual Terhadap Perkembangan Bahasa dalam Hal Menyimak dan Berbicara Pada Anak Taman Kanak-Kanak Kelompok B di Gugus III Kecamatan Paron Ngawi - Elisa Novie Azizah (SELING: Jurnal Program Studi PGRA, 2016)
Based on the result of first observation found that students of Kindergarten group B cluster III Paron Ngawi regency tend to have short listening effort in receiving information, and lack of vocabulary to tell information with their own language. It is dueto the learning method used by the teacher tends to be monotonious and less of using learning media in the learning process. Concerning with the above problem, the researcher conducts the research which is aimed to know the influence of story telling method using audio-visual towards the language development especially in listening and speaking.beside, this research is conducted because of memorizing that listening and speaking skill are as basic fundamental human activities to own creativity and high imagination that show more or less idioms (vocabulary) through their own language.